Local wisdom behind traditions in Madura District Indonesia - M. Sahid, Dian Eka Indriani; Syaiful Bachri, Bachtiar; Anugerah Izzati, Umi (Opción, 2019)
The aim of the study is to investigate local wisdom behind traditions in Madura district Indonesia via ground theory with literature study. As a result, peace and conflict prevention will be more felt when local wisdom is supported, facilitated, and assisted by the role of the state and government. But local wisdom has not yet been fully accommodated by the government as an authorized party or from public awareness itself. In conclusion, there are one or two traditions found that can be at the root of the conflict, such as the existence of carok in Madura